EMOTIONAL INTELLIGENCE DAN KEBERHASILAN PEMBELAJARAN BAHASA ARAB - Fitriyanti, Fitriyanti; Wahananto, Juri; Mufidah, Nuril (Lembaga Pendidikan Ma'arif Nahdlatul Ulama, Kabupaten Malang, Indonesia, 2024)
Emotional Intelligence in the Success of Arabic Language: An Exploration of the Role of Emotional Intelligence in Enhancing Language Skills and Cultural Understanding. This study aims to investigate the relationship between emotional intelligence and the success of Arabic language learners. Emotional intelligence is a vital component in the process of language acquisition, as it enables individuals to navigate the complexities of language and cultural nuances effectively. The study focuses on the role of emotional intelligence in enhancing language skills and cultural understanding among Arabic language learners. It explores the impact of emotional intelligence on language proficiency, vocabulary acquisition, and cultural competence, and examines the strategies that learners employ to manage their emotions and overcome language barriers. The findings of this study have implications for language teaching and learning, highlighting the importance of incorporating emotional intelligence training into language education programs to improve learner outcomes and enhance cross-cultural communication.